HUBUNGAN SIKAP TERHADAP BLENDED LEARNING DENGAN MOTIVASI BELAJAR MAHASISWA PROGRAM STUDI KEDOKTERAN UNIVERSITAS MUHAMMADIYAH JAKARTA TAHUN 2021 - Afifah Jihan Amalia (2022)
Background: At present, industrial revolution 4.0 is a new era in globalization. Japan assessed that the industrial revolution 4.0 had the potential to reduce the role of humans, so Japan created a concept called Society 5.0. Learning in the era of industrial revolution 4.0 towards society 5.0 from the point of view of education management is achieved by bringing together various aspects that affect the achievement of national education goals. The start of vaccination in Indonesia has impacted various fields, one of which is education. Several educational institutions have started learning activities using the blended learning method. This study aims to find out whether there is a relationship between attitudes towards blended learning and student motivation in the Medical Study Program, the University of Muhammadiyah Jakarta in 2021. Methods: The research was conducted using an analytical observational research design with a cross-sectional approach. Respondents in this study included medical students at the University of Muhammadiyah Jakarta batch 2019, 2020, and 2021 who took part in lecture activities using the blended learning method. Primary data is the type of data used and obtained from filling out a questionnaire. Results: The results showed that 81 students (77.1%) had a positive attitude towards blended learning and 77 students (73.3%) had high learning motivation. The results of the Kruskal-Wallis test showed a relationship between attitudes towards blended learning and students' learning motivation (p = 0.048). Conclusion: Most respondents have a positive attitude towards blended learning with high learning motivation. Keywords: Attitudes Towards Blended Learning, Learning Motivation, Medical Students